A delay-bounded low-cost multicast routing algorithm for mobile ad hoc networks. Issue 2 (April 2021) - Miao, Xuna; Wu, Xiaobo
In this paper, we focus on developing delay-bounded low-cost multicast tree, linking a source to a set of multicast nodes in a mobile ad hoc network The problem of our concern is given a wireless ad hoc network and a multicast request, how to find a multicast tree such that the total cost of the multicast tree is minimized, the cost can be regarded as transmitting power, bandwidth, battery energy, and so on. We proposed a novel minimum-cost multicast routing heuristic algorithm (delay-bounded low-cost multicast routing algorithm) to solve this well-known hard problem, and this algorithm can be easily implemented in a distributed fashion. The algorithm guarantees the multicast tree, which satisfies the delay bound and has low cost if it exists. And finally, the performance of mobile ad hoc network scared from 50 to 200 nodes is evaluated. Simulations results show that the delay and tree cost of the proposed method are lower than well-known multicast ad hoc on-demand distance vector protocol and QoS Dependent Multicast Routing protocol.